2017
DOI: 10.1039/c6cc08109f
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent iridium(iii) complexes as COX-2-specific imaging agents in cancer cells

Abstract: Two luminescent iridium(iii) complexes, 1 and 2, were synthesized and evaluated for their ability to probe COX-2 in human cancer cells. This is the first application of iridium(iii) complexes as imaging agents for COX-2. We demonstrate that complex 1 differentiates cancer cells from normal cells with high stability and low cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…In the literature there are diverse data considering COX expression in different cell lines [66][67][68][69]. HeLa, HT-29 and MCF-7 cell lines have high expression of COX-1, but relatively low of COX-2 [70][71][72]. Metamizole and its metabolites have been shown to inhibit COX-1 and COX-2 activity by a different pathway than the classical aspirin-like NSAIDs mechanism [73].…”
Section: Dapi Stainingmentioning
confidence: 99%
“…In the literature there are diverse data considering COX expression in different cell lines [66][67][68][69]. HeLa, HT-29 and MCF-7 cell lines have high expression of COX-1, but relatively low of COX-2 [70][71][72]. Metamizole and its metabolites have been shown to inhibit COX-1 and COX-2 activity by a different pathway than the classical aspirin-like NSAIDs mechanism [73].…”
Section: Dapi Stainingmentioning
confidence: 99%
“…Instead, a non-covalent interaction between the probe and the analyte changes the local environment of the probe, triggering a luminescence response [41,42]. In contrast, in the covalent mechanism, a chemical reaction takes place between a functional group on the sensing probe and the target analyte [43,44], producing novel products with different optical properties, such as wavelength and emission intensity, compared to the starting materials [45].…”
Section: Principle Of Metal Complex-based Chemosensorsmentioning
confidence: 99%
“…Ma, Leung and co-workers have recently developed two luminescent iridium(III) complexes 5a and 5b (Fig. 5a) for the sensing of COX-2 in human cancer cells [44]. These complexes conjugate the well-known COX-2 inhibitor, indomethacin, on an iridium(III) scaffold.…”
Section: Iridium(iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Boyer-Di Ponio et al (15), showed that the missense mutant protein C284F as well as truncated proteins E1003X and Δ4 impaired activation of Notch signaling, suggesting that a dominant-negative effect mechanism may also explain the impaired biological function of some ALGS mutations. Biomarker detection was widely used to monitor the development of certain diseases (17)(18)(19). The finding that the developing heart was more sensitive to a decreased dosage of JAG1 than the developing liver implicates JAG1 as a plausible candidate biomarker for cardiac severity in ALGS (20).…”
Section: Introductionmentioning
confidence: 99%